2023
DOI: 10.1038/s41467-023-37984-x
|View full text |Cite
|
Sign up to set email alerts
|

A small secreted protein NICOL regulates lumicrine-mediated sperm maturation and male fertility

Abstract: The mammalian spermatozoa produced in the testis require functional maturation in the epididymis for their full competence. Epididymal sperm maturation is regulated by lumicrine signalling pathways in which testis-derived secreted signals relocate to the epididymis lumen and promote functional differentiation. However, the detailed mechanisms of lumicrine regulation are unclear. Herein, we demonstrate that a small secreted protein, NELL2-interacting cofactor for lumicrine signalling (NICOL), plays a crucial ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…These defects observed in Nicol KO males were all restored by the testis-specific expression of Nicol transgene (Kiyozumi et al, 2023). Interestingly, the in vitro experiment using purified recombinant proteins showed that NICOL forms a tight molecular complex with NELL2 (Kiyozumi et al, 2023). Collectively, the data suggest that NICOL-NELL2 complex is the functional unit of the testicular lumicrine factor that binds and stimulates ROS1 to trigger initial segment differentiation.…”
Section: Lumicrine: a Testis-epididymis Transluminal Signaling System...mentioning
confidence: 84%
See 4 more Smart Citations
“…These defects observed in Nicol KO males were all restored by the testis-specific expression of Nicol transgene (Kiyozumi et al, 2023). Interestingly, the in vitro experiment using purified recombinant proteins showed that NICOL forms a tight molecular complex with NELL2 (Kiyozumi et al, 2023). Collectively, the data suggest that NICOL-NELL2 complex is the functional unit of the testicular lumicrine factor that binds and stimulates ROS1 to trigger initial segment differentiation.…”
Section: Lumicrine: a Testis-epididymis Transluminal Signaling System...mentioning
confidence: 84%
“…Thus, the defective initial segment differentiation, defective sperm maturation, defective sperm migration from uterus into oviduct, and male infertility observed in Nicol KO mice are phenocopies of defects observed in Nell2 KO or Ros1 KO mice. These defects observed in Nicol KO males were all restored by the testis-specific expression of Nicol transgene (Kiyozumi et al, 2023). Interestingly, the in vitro experiment using purified recombinant proteins showed that NICOL forms a tight molecular complex with NELL2 (Kiyozumi et al, 2023).…”
Section: Lumicrine: a Testis-epididymis Transluminal Signaling System...mentioning
confidence: 95%
See 3 more Smart Citations